France’s Nuclear Defence Strategy towards the Prospects for European Nuclear Deterrence - Tomasz Młynarski (Politeja)
The crisis of multilateralism and the growing strategic and military rivalry between superpowers is changing the stability and balance of forces in the world. The war in Ukraine has put nuclear weapons and their role in Europe’s defence back at the centre of the security debate. To maintain its international position and effectively protect its interests, France cannot afford to weaken its main asset – nuclear deterrence forces. That is why President Emmanuel Macron has announced the maintenance of strategic autonomy and has also offered dialogue for a greater role and participation of Europeans in common defence. The article focuses on France as a case study and examines the motivations of the French authorities to formulate a strong push for the Europeanisation of nuclear deterrence based on French capabilities. The employment of historical and comparative methodology, comprising the analysis of document content, statements and official reports, augmented by interviews with experts and key policymakers, has permitted the tracing of the evolution of the French nuclear deterrent. This provides a research context for President Emmanuel Macron’s current policy and his proposals relating to the role of French nuclear deterrence in Europe. The aim of this study is to analyse and explain the role of French nuclear deterrence forces in creating a nuclear deterrent at a European level and promoting a nuclear culture among European allies. This article, which explores how the French nuclear strategy is shaped by historical circumstances and current geopolitical needs, makes a threefold contribution to the literature: firstly, it discusses the historical background to the development of the French doctrine of nuclear deterrence; secondly, it presents the main principles of the French nuclear deterrent; and thirdly, it demonstrates that France is not in a  position to rapidly provide an extended nuclear deterrent for Europe but can make a significant contribution to the collective security of European Union states.